STRUCTURAL STUDY AND THE EFFECT OF IONIC SIZE OF THE SYSTEMS (Gd1-x LuX) 3Al5 O12 DOPED ERBIUM. - Lanez, I; Rekik, B; Derbal, M; Chaib, A (university of eloued -جامعة الوادي, 2019)
The structure of cubicGarnetsmulti-componentsbased on Gadolinium (GAG)undopedor doped rare earth,stabilized by Lanthanide as Lutetium,which has weak ionic radiusrecently attracts much attention to obtain the phasesthermodynamically stables.In this work, we have chosento studythe development of compositions of type (Gd1 -x Lux) 3Al5O12(x = 0, 2 -0, 3)doped 2and 5 at %Er+3. The polycrystalline powders were prepared by reactionsolid statemethod. DRXanalyses on thesesynthesized powders confirmed the results of the phases of GdAlO3perovskiteandGd3Al5O12garnet dueto the highercontent of gadoliniumstabilized by Lutetium. FTIRanalyses have shown the active vibrations modes associated on the specifics absorption bandsof M –O (M: metallic elements Gd and Lu or Al).The optical analyzes carried out by the photoluminescence spectroscopy which it study the transitions of Erbium (Er3+)as doping elements in elaborated samples is of great optical importance
article
Keywords: Cubic Garnets, ionic radius, Perovskite, DRX, FTIR, Photoluminescence spectroscopy.